2020
DOI: 10.1111/jam.14553
|View full text |Cite
|
Sign up to set email alerts
|

An endophyticPenicillium oxalicumisolated fromCitrus limonpossesses antioxidant and genoprotective potential

Abstract: Aims: This study aimed at isolating endophytic fungi from Citrus limon (L.) possessing antioxidative and genoprotective potential. Methods and Results: Endophytic fungi were screened for antioxidant activity using 2,2-diphenyl,1-picryl hydrazyl radical scavenging assay and maximum activity (79Á70%) was exhibited by culture MP1 identified to be Penicillium oxalicum on the basis of morphological and molecular characteristics. The ethyl acetate extract of MP1 was subjected to silica column chromatography followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…However, A. flavus have been reported with significant antioxidant activity and with a positive correlation with the phenolic content. The DPPH free radical scavenging activity of EA extract of P. oxalicum was in accordance with previous study, which showed that fungal endophyte P. oxalicum isolated from Citrus limon showed linear correlation between high phenolic content and DPPH scavenging activity with an EC 50 value of 127.56 µg/mL [44]. The metabolites N-[2-(4 hydroxyphenyl) ethenyl] formamide and tuckolide isolated from P. oxalicum were effective against DPPH radical scavenging assay with EC 50 values of 18.53 and 79.17 µg/mL, respectively [45].…”
Section: Ea Extract Of a Flavus And P Oxalicum Shows Potential Free R...supporting
confidence: 91%
“…However, A. flavus have been reported with significant antioxidant activity and with a positive correlation with the phenolic content. The DPPH free radical scavenging activity of EA extract of P. oxalicum was in accordance with previous study, which showed that fungal endophyte P. oxalicum isolated from Citrus limon showed linear correlation between high phenolic content and DPPH scavenging activity with an EC 50 value of 127.56 µg/mL [44]. The metabolites N-[2-(4 hydroxyphenyl) ethenyl] formamide and tuckolide isolated from P. oxalicum were effective against DPPH radical scavenging assay with EC 50 values of 18.53 and 79.17 µg/mL, respectively [45].…”
Section: Ea Extract Of a Flavus And P Oxalicum Shows Potential Free R...supporting
confidence: 91%
“…Penicillium is another fungal endophytic genus studied in more detail with high antioxidant activity [7,54]. In berries, two of the Penicillium crustosum isolates showed high antioxidant activity (23.9 and 19.1 mg AA L −1 ) which is in connection with previous studies [7,55,56]. Other fungal endophytes with high antioxidant activity are Fusarium sp.…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…It was found that the DMP1 fungus had DNA similarity with the fungus Penicillium oxalicum isolate HC6 (MH558553) 25 with 100% similarity (figure 1). Penicillium oxalicum is one of the fungi whose extracts are widely used as an anti-fungal, anti-microbial and antioxidant 26,27,28 . The ethyl acetate extract of the fungus Penicillium oxalicum inhibited the peroxidation of linoleic acid by 78% 29 .…”
Section: Resultsmentioning
confidence: 99%